Colisión de derechos constitucionales entre la libertad de expresión y el derecho a la honra en el juzgamiento a funcionarios públicos y representantes políticos - Moreno Espinosa, Paula Sophia (2018)
This thesis has been constituted on the basis of a legal, doctrinal and historical study, in which I have protected myself to strengthen my hypothesis, which is based on the idea that freedom of expression is above the disagreement felt by those who They have received unfavorable expressions, when in a democratic state, the citizen in search of reasons issues comments that may be offensive to public officials and political representatives, who according to my study should be tolerant of this type of confrontation, since society will be very interested in the performance of their work, because their functions are at the service of the population, then there is a collision that makes two very important rights for the development of each individual within their social circle, come to face, generating a very complicated disjunctive.